Bumiputera corporate equity ownership and value relevance within the integrated reporting framework / Nahariah Jaffar, Norazlan Alias, Noor Adwa Sulaiman and Zarehan Selamat - Jaffar, Nahariah; Alias, Norazlan; Sulaiman, Noor Adwa; Selamat, Zarehan (UiTM Press, 2023)
The purpose of this study was to examine the effect of disclosure of information on Bumiputera corporate equity ownership on value relevance of corporate information in the Malaysian companies within the Integrated Reporting Framework. Data were collected from annual reports of 603 companies for the year 2015. These companies were listed on the Main Market of Bursa Malaysia. Results showed that the disclosure of information regarding the Bumiputera corporate equity ownership, information related to three Integrated Report content elements, namely organizational overview and external environment, company’s outlook, and basis of presentation; and total assets and book value were found to affect the firm value significantly and positively. However, the disclosure of the information concerning basis of presentation had a negative effect on value relevance of the companies’ corporate information. The findings offer evidence pertaining the potential impact of information related to Bumiputera corporate equity ownership and content elements of an integrated report on the value relevance of corporate information in Malaysia.